Analisis Hukum Islam Terhadap Sertifikat Halal Pada Produk Makanan (Roti) Di Kota Padang - Islami, Aufa (TAWAZUN: Journal of Sharia Economic Law, 2022)
This research is motivated by food entrepreneurs (bread) in the city of Padang who still include the halal label without extending the halal certificate on the food (bread). This study was conducted to find out how the implementation of halal labels on food packaging (bread) in the city of Padang, and to find out how the review of Islamic law regarding the use of halal labels in the city of Padang. This type of research is a field research (field research), the nature of this research is descriptive-analytical. Collecting data using observation and interview methods. Then in processing the data, after collecting the data it will be examined, classified and analyzed the data. By drawing conclusions using a qualitative descriptive research approach. The results of the study show a review of Islamic law regarding the use of halal labels in the city of Padang are: a). The food entrepreneur (bread) has a halal certificate from the LP POM MUI and the halal certificate is still valid and extended, the product being sold or marketed is legal in eating it is halal. b) Food entrepreneurs (bread) have a halal certificate from LP POM MUI but are not valid and do not extend the halal certificate, food products (bread) that are sold or in the market are legal to eat them, c) The law on consuming food (bread) that is not registered and getting a halal certificate becomes doubtful if this is viewed from Islamic law.